Human stem cell models for Marfan syndrome: a brief overview of the rising star in disease modelling - Jeffrey Aalders; Laura Muiño Mosquera; Laura Muiño Mosquera; Jolanda van Hengel (Frontiers in Cell and Developmental Biology)
The introduction of pluripotent stem cells into the field of disease modelling resulted in numerous opportunities to study and uncover disease mechanisms in a petri dish. This promising avenue has also been applied to model Marfan syndrome, a disease affecting multiple organ systems, including the skeletal and cardiovascular system. Marfan syndrome is caused by pathogenic variants in FBN1, the gene encoding for the extracellular matrix protein fibrillin-1 which ensembles into microfibrils. There is a poor genotype-phenotype correlation displayed by the diverse clinical manifestations of this disease in patients. Up to now, 52 different human pluripotent stem cells lines have been established and reported for Marfan syndrome. These stem cells have been employed to model aortopathy, skeletal abnormalities and cardiomyopathy in vitro. These models were able to recapitulate key features of the disease that are also observed in patients. The use of pluripotent stem cells will help to uncover disease mechanisms and to identify new therapeutic strategies in Marfan syndrome.